Toll-Like Receptor 4 Is Essential for the Expression of Sphingosine-1-Phosphate-Dependent Asthma-Like Disease in Mice - Roviezzo, Fiorentina; Sorrentino, Rosalinda; Terlizzi, Michela; Riemma, Maria Antonietta; Iacono, Valentina Mattera; Rossi, Antonietta; Spaziano, Giuseppe; Pinto, Aldo; D’Agostino, Bruno; Cirino, Giuseppe (Frontiers in Immunology, 2017)
Sphingosine-1-phosphate (S1P) levels significantly increase in bronchoalveolar lavage (BAL) of asthmatic patients following segmental allergen challenge and this increase well correlates with pulmonary inflammation. Epidemiological, genetic, clinical and experimental data indicate a potential for the Toll-like receptor 4 (TLR4) to initiate and exacerbate allergic airway disease. The aim of this study was to evaluate the contribute of TLR4 in S1P-dependent asthma-like disease in mice. BALB/c or TLR4 defective (C3H/HeJ) mice received S1P (10ng/mouse), LPS (0.1µg/mouse) or S1P+LPS. Furthermore, S1P-treated BALB/c mice were injected with the purified rabbit anti-TLR4 antibody (10µg/mouse). S1P administration induced airway hyperreactivity and pulmonary inflammation associated to an increase in the percentage of dendritic cells and macrophages into the lung of BALB/c mice. These effects were coupled to a reduction of dendritic cells in the mediastinic lymph node. All these S1P-mediated effects were absent in TLR4 defective mice or reversed by treatment with a purified rabbit anti-TLR4 antibody. Confocal analysis of pulmonary sections showed a significant increase in TLR4+ cells and a similar presence of S1P1 and TLR4 following S1P challenge. Accordingly, the immunoprecipitation evidenced an increased S1P1/TLR4 interaction. In conclusions, our findings suggest thata functional interaction between S1P1 and TLR4 leads to an enhanced allergic inflammatory response. Thus, S1P pathway contributes to the sentinel role played by innate immunity providing new targets for prevention and treatment of allergic airway diseases.